Risk Stratification for Sudden Cardiac Death in Heart Failure - Hendry Purnasidha Bagaswoto (ACI (Acta Cardiologia Indonesiana), 2019)
Heart failure (HF) is a complex clinical syndrome in which structural / functional myocardial abnormalities result in symptoms and signs of hypoperfusion and/or pulmonary or systemic congestion at rest or during exercise. More than 80% of deaths in patients with HF recognize a cardiovascular cause, with most being either sudden cardiac death (SCD) or death caused by progressive pump failure. Risk stratiﬁcation of SCD in patients with HF represents a clinical challenge. This review will give an update of current strategies for SCD risk stratiﬁcation in HF.